PENGARUH KOMITMEN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK MANDIRI (PERSERO) TBK DIVISI MIKRO CLUSTER SUDIRMAN SAMARINDA - La Robby (OBOR: Oikonomia Borneo, 2019)
The purpose of this study was to determine the effect of work commitment and work stress partially or simultaneously significant effect on employee performance at PT. Bank Mandiri (Persero) Tbk Sudirman Cluster Micro Division Samarinda. From the results of the analysis, it is known that the Multiple Linearity is Y = 6.946X 0.716 + 0.108, this indicates that work commitment and work stress have a positive effect on employee performance. As for the results of the Coefficient of Determination analysis, it is known that R^2 = 0.535, this shows that there is an influence of 5.35% between Work Commitment and Work Stress on Employee Performance. And based on the results of hypothesis testing H1 work commitment has a significant effect on performance, H2 work stress has no significant effect on performance, and H3 simultaneously between work commitment and work stress has a significant effect on employee performance.